Electricity consumption and economic growth: A revisit study of their causality in Malaysia - Mohd Thas Thaker, M. A.; Mohd Thas Thaker, Hassanudin *; Amin, M.; Allah Pitchay, A. (Faculty of Economics, Universitas Islam Indonesia, 2019)
The role of electricity towards the economy becomes crucial in many countries including in Malaysia. It becomes necessary to investigate whether electricity consumption contributes to economic growth in order to make appropriate energy policies. The purpose of this research is to examine the long run and causal relationships between electric power consumption and real GDP. This paper applies to the error-correction model. The results indicate that electricity consumption has a positive impact on economic growth. Besides that, there was unidirectional Granger causality running from electricity consumption to real GDP but not vice versa. This paper suggests that Malaysia is becoming an energy-dependent country. The government should emphasize on formulating energy strategies so as to avoid adverse effects on economic growth